Covid-19 and Its Impact on Education (Physical Learning and Teaching with 3R's) - Yagnik, Shilpa Trivedi; Yagnik, Vinit (Journal of Commerce and Trade, 2021)
When COVID-19 engulfed the entire world, no one would have guessed that it would change the lifestyle of people everywhere. However, with the COVID-19 impact, adopting a new normal was a significant change that included WFH, lifting loads of precautionary measures into our daily lives, and the closure of parks, offices and another central facility- school and other educational institutions! Yes, the government initially decided to close schools to reduce the spread of COVID-19 temporarily, but this increased the infection rate. The pandemic opened the doors to innovative ways of learning, and efforts were made to help all students with online learning methods. The adoption of modern digital technologies accelerated learning, and educational institutions encouraged teachers and students to work with webinars, virtual classrooms, digital assessments and exams for better learning from home. Although the outbreak of COVID-19 had many positive effects on the education sector, the negative impacts should not be ignored. Many students, who did not have the resources to attend online classes, faced much trouble and struggled to get gadgets to attend online classes. The academic activities got hampered due to too much confusion and delayed the exams and other sessions. Teachers who use books, chalk, blackboards and classroom methods for traditional teaching methods had to be trained to deal with the current teaching state.